2007
DOI: 10.1158/1535-7163.mct-06-0648
|View full text |Cite
|
Sign up to set email alerts
|

Combined targeting of epidermal growth factor receptor and hedgehog signaling by gefitinib and cyclopamine cooperatively improves the cytotoxic effects of docetaxel on metastatic prostate cancer cells

Abstract: The epidermal growth factor receptor (EGFR) and hedgehog cascades provide a critical role in prostate cancer progression and contribute to the resistance to clinical therapies and disease relapse. Therefore, we evaluated, for the first time, the antiproliferative and cytotoxic effects induced by a combination of selective inhibitors of EGFR tyrosine kinase and smoothened hedgehog signaling element, gefitinib and cyclopamine, with a current chemotherapeutic drug used in the clinics, docetaxel, on some metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
90
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 66 publications
8
90
0
Order By: Relevance
“…These observations, which are consistent with a reduction of the bulk mass of proliferative androgen sensitive PC cells, while AI PC cells with stem cell-like features can persist after AR inhibition, underline the importance of using casodex in combination with other cytotoxic drugs for eradicating the total PC cell mass (108). Of particular interest, the blockade of EGFR and/or hedgehog cascades by using a specific inhibitor of EGFR tyrosine kinase activity (such as gefitinib, erlotinib or lapitinib), smoothened (SMO) hedgehog coreceptor inhibitor, cyclopamine or anti-SHH antibody has also been shown to induce the antiproliferative, antiinvasive and cytotoxic effects on PC stem/ progenitor cells with stem cell-like properties and their progenies in vitro and in vivo (Figure 3) (14,15,21,22,69,203,209,210). For instance, it was reported that the cotargeting of EGFR and hedgehog pathways by using gefitinib and cyclopamine improved the cytotoxic effects induced by mitoxantrone on parental AI PC3 and DU145 cells and CD44 high cell fractions enriched from these metastatic PC cell lines (203).…”
Section: Other Anticancer Agents Targeting Pc-and Metastasis-initiatimentioning
confidence: 99%
See 1 more Smart Citation
“…These observations, which are consistent with a reduction of the bulk mass of proliferative androgen sensitive PC cells, while AI PC cells with stem cell-like features can persist after AR inhibition, underline the importance of using casodex in combination with other cytotoxic drugs for eradicating the total PC cell mass (108). Of particular interest, the blockade of EGFR and/or hedgehog cascades by using a specific inhibitor of EGFR tyrosine kinase activity (such as gefitinib, erlotinib or lapitinib), smoothened (SMO) hedgehog coreceptor inhibitor, cyclopamine or anti-SHH antibody has also been shown to induce the antiproliferative, antiinvasive and cytotoxic effects on PC stem/ progenitor cells with stem cell-like properties and their progenies in vitro and in vivo (Figure 3) (14,15,21,22,69,203,209,210). For instance, it was reported that the cotargeting of EGFR and hedgehog pathways by using gefitinib and cyclopamine improved the cytotoxic effects induced by mitoxantrone on parental AI PC3 and DU145 cells and CD44 high cell fractions enriched from these metastatic PC cell lines (203).…”
Section: Other Anticancer Agents Targeting Pc-and Metastasis-initiatimentioning
confidence: 99%
“…It has been shown that the sustained activation of epidermal growth factor receptor (EGFR), hedgehog, Wnt/β-catenin, hyaluronan (HA)/CD44, transforming growth factor (TGF)-β/ TGF-βR receptors and stromal cell-derived factor-1 (SDF-1)/ CXC chemokine receptor 4 (CXCR4) frequently occurs during PC progression to locally invasive and metastatic CRPCs (5,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). These tumorigenic cascades can account for the sustained growth, survival, invasion, metastases and treatment resistance of PC cells.…”
Section: Introductionmentioning
confidence: 99%
“…GLI target gene activation and specificity was shown to be affected by PKCd (Riobo et al, 2006a;Lauth et al, 2007), Akt/ PI3K (Riobo et al, 2006b), RAS/MEK/ERK (Pasca di Magliano et al, 2006;Stecca et al, 2007;Neill et al, 2008) and EGF signaling (Bigelow et al, 2005;Kasper et al, 2006b;Mimeault et al, 2007). However, the integration of different upstream signals by co-activators and other modulators on GLI target gene promoters is still far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…Two contemporary Smotargeting agents, GDC-0449 and IPI-926, are already subject to clinical testing in human patients [86][87][88]. Use of GDC-0449 alone in Phase I testing has already demonstrated evidence of objective responses for some cancers [88] and investigators are already considering the possible benefit of combining Smo-targeting drugs with other targeted therapeutics for cancers [89] to improve the response. Considering the evidence that many solid tumors benefit from a paracrine hedgehog signaling environment, Smo-targeting drugs could provide an adjuvant therapy to suppress the hedgehog signaling microenvironment of the tumor and open clinical trials for GDC-0049 are actively accruing patients with these alternate solid tumors.…”
Section: Hedgehog and Human Cancersmentioning
confidence: 99%